2003
DOI: 10.1007/s00442-003-1344-y
|View full text |Cite
|
Sign up to set email alerts
|

Founder population size and number of source populations enhance colonization success in waterstriders

Abstract: Understanding the factors that underlie colonization success is crucial both for ecological theory and conservation practices. The most effective way to assess colonization ability is to introduce experimentally different sets of individuals in empty patches of suitable habitat and to monitor the outcome. We translocated mated female waterstriders, Aquarius najas, into 90 streams that were not currently inhabited by the species. We manipulated sizes of propagules (from 2 to 16 mated females) and numbers of ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 20 publications
(32 reference statements)
0
67
1
1
Order By: Relevance
“…Some of these other studies are in fact based on experimental tests of the effect of propagule pressure (e.g. Grevstad 1999;Ahlroth et al 2003;Memmott et al 2005; see also Simberloff 2009). For example, Memmott et al (2005) found a positive relationship between propagule size and establishment probability from field experimental releases of the alien psyllid Arytainilla spartiophila.…”
Section: Re-analysis Of the New Zealand Bird Introduction Datamentioning
confidence: 98%
“…Some of these other studies are in fact based on experimental tests of the effect of propagule pressure (e.g. Grevstad 1999;Ahlroth et al 2003;Memmott et al 2005; see also Simberloff 2009). For example, Memmott et al (2005) found a positive relationship between propagule size and establishment probability from field experimental releases of the alien psyllid Arytainilla spartiophila.…”
Section: Re-analysis Of the New Zealand Bird Introduction Datamentioning
confidence: 98%
“…Individuals are also relatively easy to monitor, because all of their movements occur within streams. Moreover, in most cases individuals move less than 300 m in their lifetime from their natal stream (Ahlroth et al 1999(Ahlroth et al , 2003. Within each river basin lakes represent dispersal barriers to A. najas, because it has a strong preference for relatively rapidly flowing water.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these studies have not yet led to a consensus. They have found that demography [16], genetics [15,17] or both demography and genetics [14] can be responsible for initial establishment success (table 1). Subsequent performance of newly established populations depend either on the genetic background of founders [15,17] or on demography and genetics together [18,19].…”
Section: Introductionmentioning
confidence: 99%